The Effect Of Organizational Culture On Employee Performance In The Masaran Batik Industry, Sragen, Central Java - Hakim, Lukman; Sugiyanto, Eko (Prosiding University Research Colloquium, 2022)
Organizational culture is a system of shared meanings (perceptions) held by members of the organization, which distinguishes the organization from other organizations. The aims of this study are: (1) To examine the effect of superior organizational culture models/characteristics on employee performance in the Masaran Batik Industry, Sragen, Central Java. (2) Identifying the values behind the influence of superior organizational culture on employee performance in the Masaran Batik Industry, Sragen, Central Java. In this research, the locations are three Masaran batik industries, Sragen, Central Java, namely Brotojoyo Batik, Dewi Ratih Batik and Aluna Batik. The model in this study will be tested using multiple regression analysis. Then to find out the significance of the correlation coefficient of each variable, a series of tests were carried out, namely the simultaneous test (F test) and partial test (t test). The results of the study show that together the variables of a culture of transparency, a culture of thoroughness, a dynamic culture, a culture of professionalism, and a culture of togetherness have an influence on employee performance.